How Does the Environmental Approach Work in Learning Materials Responding to an Issue About the Covid-19 Pandemic? - Catur Endang Lestari (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Language is something important that we always use in our daily life. Language is increasingly developing along with the progress of the times, as well as in Indonesian which is increasingly advanced and developing. In the process of teaching and learning activities in the classroom, of course, they must refer to and be guided by the applicable curriculum. However, this seems to be something that feels heavy for educators because it requires a qualified understanding and ability to apply it. Learning methods and media are strategic combat tools for teachers in implementing the teaching and learning process. Learning methods tend to be prescriptive, which is relatively difficult to distinguish from learning strategies. Students are asked to be more sensitive to events or phenomena that occur in the surrounding environment, then make the learning material. One of the basic competencies that grade V students must achieve is being able to respond to an event or phenomenon. In order to understand more quickly, teachers can guide students by providing renewable themes, for example about the pandemic currently hitting the world, namely Coronavirus or COVID-19. Keywords: environmental approach, responding to problems, the COVID-19 pandemic Abstrak Bahasa adalah sesuatu hal yang penting yang selalu kita gunakan dalam kehidupan sehari-hari. Bahasa semakin berkembang seiring dengan laju kemajuan zaman, begitupun dalam bahasa Indonesia yang kian maju dan berkembang. Dalam proses kegiatan belajar mengajar di kelas tentunya harus mengacu dan berpedoman kepada kurikulum yang berlaku. Namun, hal ini sepertinya menjadi suatu hal yang terasa berat bagi para pendidik karena hal itu memerlukan pemahaman dan kemampuan yang mumpuni untuk menerapkannya. Metode dan media pembelajaran adalah alat tempur dalam berstrategi bagi pengajar dalam pelaksaan proses belajar-mengajar. Metode pembelajaran cenderung preskriptif, yang relatif sulit dibedakan dengan strategi pembelajaran. Siswa diminta lebih peka terhadap peristiwa atau fenomena yang terjadi di lingkungan sekitarnya, lalu menjadikan bahan pelajarannya. Salah satu kompetensi dasar yang harus dicapai siswa kelas V adalah mampu menanggapi suatu peristiwa atau fenomena. Agar lebih cepat memahami, guru bisa membimbing siswa dengan memberikan tema yang terbarukan, misalnya tentang pandemi yang sedang melanda dunia, yaitu Coronavirus atau COVID-19. Kata kunci: pendekatan lingkungan, menanggapi persoalan, pandemi COVID-19